2015
DOI: 10.1016/j.neo.2014.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Profiling by HRMAS NMR Spectroscopy of Pheochromocytomas and Paragangliomas Detects SDH Deficiency: Clinical and Pathophysiological Implications

Abstract: Succinate dehydrogenase gene (SDHx) mutations increase susceptibility to develop pheochromocytomas/paragangliomas (PHEOs/PGLs). In the present study, we evaluate the performance and clinical applications of 1H high-resolution magic angle spinning (HRMAS) nuclear magnetic resonance (NMR) spectroscopy–based global metabolomic profiling in a large series of PHEOs/PGLs of different genetic backgrounds. Eighty-seven PHEOs/PGLs (48 sporadic/23 SDHx/7 von Hippel-Lindau/5 REarranged during Transfection/3 neurofibromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 36 publications
1
57
0
Order By: Relevance
“…Interestingly, in an Sdhb À/À mouse tumor model, this succinate peak is correlated with the concentrations of succinate measured in the resected tumors by GC-MS. Demonstration of SDH inactivation is currently based on in vitro analyses of tissue samples: immunohistochemical analyses of SDHB, SDHA, and SDHD expression in FFPE tissues (16,18,22), direct succinate measurements on frozen tumor samples by nuclear magnetic resonance (NMR) spectroscopy (15,19,20,23), GC-MS, or liquid chromatography mass spectroscopy (LC-MS; refs. 13,17,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in an Sdhb À/À mouse tumor model, this succinate peak is correlated with the concentrations of succinate measured in the resected tumors by GC-MS. Demonstration of SDH inactivation is currently based on in vitro analyses of tissue samples: immunohistochemical analyses of SDHB, SDHA, and SDHD expression in FFPE tissues (16,18,22), direct succinate measurements on frozen tumor samples by nuclear magnetic resonance (NMR) spectroscopy (15,19,20,23), GC-MS, or liquid chromatography mass spectroscopy (LC-MS; refs. 13,17,21).…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers could serve as surrogate markers in the assessment of tumor response to specific treatments. Until now, no in vivo method to assess the functional consequences of SDHx mutations was available, and all existing tests were performed on surgical resected specimens (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…SDHx -related PPGLs dramatically accumulate succinate as a result of a TCA blockade that is detectable by ex vivo [4951] and in vivo proton MR spectroscopy [52, 53]. …”
Section: B Emerging Stromal Cell-succinate-18f-fdg Imaging Phenotypementioning
confidence: 99%
“…A consequence of the enzymatic loss of function is the accumulation in the cytoplasm of the corresponding substrate. Two different groups demonstrated that in SDHx mutated pheochromocytoma/paraganglioma tumor tissues succinate levels are significantly higher than in WT tumors (Pollard et al 2005, Lendvai et al 2014, Imperiale et al 2015. The defect of enzymatic activity is associated not only with an impairment of the TCA cycle but also to changes in the structure of mitochondria that appear increased in number, swollen, and with a significant reduction of the internal cristae (Fig.…”
Section: Mitochondria Impairment and Pheochromocytoma/paragangliomamentioning
confidence: 97%